PENGARUH MOTIVASI SOSIAL, PENGETAHUAN AKUNTANSI DAN BIAYA PENDIDIKAN TERHADAP MINAT MAHASISWA AKUNTANSI UNTUK MENGIKUTI PENDIDIKAN PROFESI AKUNTANSI (PPAk) DENGAN MOTIVASI KUALITAS SEBAGAI VARIABEL MODERASI - Mawar Mugi Karidhani; Eliada Herwiyanti; Agus Faturokhman (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, 2022)
This study aims to determine the partial effect of social motivation, accounting knowledge, and education costs on the interest of accounting students to take PPAk with quality motivation as a moderating variable. This study also aims to determine the effect of social motivation, accounting knowledge, education costs, and quality motivation on interest in participating in PPAk. The population in this study were undergraduate students of Accounting, Faculty of Economics and Business, Jenderal Soedirman University who had taken the auditing I course and were aware of the Accounting Profession Education program. This research is a quantitative research. Sampling used the convenience proportional sampling method which resulted in 81 research samples. The data analysis technique used is Structural Equation Modeling (SEM) based on variance or variance based using Partial Least Square (PLS) alternatives. The results of this study; (1) Social motivation has a positive effect on the interest of accounting students to take PPAk, (2) Knowledge of accounting has a positive effect on the interest of accounting students to take PPAk, (3) Education costs have a negative effect on the interest of accounting students to take PPAk, (4) Quality motivation unable to moderate the influence of social motivation on the interest of accounting students to take PPAk, (5) Quality motivation is not able to moderate the effect of accounting knowledge on the interest of accounting students to take PPAk, (6) Quality motivation is not able to moderate the effect of education costs on the interest of accounting students to take PPAk.